Eurozentrismen als Erkenntnisbarrieren in der Religionswissenschaft - Ahn, Gregor (Zeitschrift für Religionswissenschaft, 1997)
From its beginning the methods and results of Religionswissenschaft have been shaped by eurocentric preconceptions as well as other contemporaneous academic subjects (i. e. Oriental Studies, Theology or Ethnology). But unlike in Ethnology Religionswissenschaft surprisingly did not treat this problem of describing foreign religions and cultures in terms of one's own. Except from some few attempts there is so far no academic debate on dealing with eurocentrism in a methodological reflected form. By differentiating terminological and systemic eurocentrism as well as terminological and contextual strategies of accomplishment a survey of the previous research on this subject will be attempted. Furthermore, a model of transforming eurocentristic conceptions into more complex schemes of cultural analysis will be presented.
Elektronische Reproduktion der Druckausgabe
Gesehen am 03.11.2023
Keywords: Religionswissenschaft; Eurozentrismus